Interrelationships among carcass characteristics of feedlot steers and heifers selected for competition - King, D.A.; Lawrence, T.E.; Schafer, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the interrelationships among carcass characteristics of steers and heifers selected from commercial feedlots for competition in the Beef Empire Days live and carcass contests. Because judging criteria are weighted heavily on cutability, the majority of cattle entered were trim and muscular. Within this highly selected group, heifer carcasses had larger ribeye areas, lower hot carcass weights, more ribeye area/100 lbs. of hot carcass weight, and a higher percentage of kidney-pelvic-heart fat than steers. However, steers graded USDA Choice or better 4% more often than heifers. Ribeye area, ribeye area/100 lbs. of hot carcass weight, and percentage of kidneypelvic- heart fat increased as dressing percentage increased; however, 12th rib fat thickness had no effect on dressing percentage. Percentage of carcasses grading USDA Choice or better tended to decrease with improved dressing percentage. As 12th rib fat thickness increased, ribeye area and ribeye area/100 lbs. of hot carcass weight decreased whereas percentage of kidneypelvic- heart fat and hot carcass weight of steers increased. As 12th rib fat thickness increased up to 0.50-0.59 inches, the percentage of cattle that graded low Choice or higher increased, but more finish did not result in further increase in percentage of low Choice or better. This study indicates that ribeye area is more closely related to economically important carcass characteristics in trim, muscular cattle than previously identified.
Keywords: Beef; Carcass characteristics; Ribeye Area; Fat thickness; Quality grade